2021
DOI: 10.3390/molecules26092677
|View full text |Cite
|
Sign up to set email alerts
|

Cocrystal of Apixaban–Quercetin: Improving Solubility and Bioavailability of Drug Combination of Two Poorly Soluble Drugs

Abstract: Drug combinations have been the hotspot of the pharmaceutical industry, but the promising applications are limited by the unmet solubility and low bioavailability. In this work, novel cocrystals, consisting of two antithrombotic drugs with poor solubility and low bioavailability in vivo, namely, apixaban (Apx) and quercetin (Que), were developed to discover a potential method to improve the poor solubility and internal absorption of the drug combination. Compared with Apx, the dissolution behavior of Apx–Que (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…Several studies have shown that quercetin protects against neurodegenerative diseases by enhancing the mechanism of SIRT1 deacetylase (203,204). However, low bioavailability and solubility of quercetin limits its clinical application (205). In addition, most of the current studies only focused on quercetin glycosides, however, the functions of the gut micobiota helps to breakdown quercetin into serious biological metabolites such as phloroglucinol, 3,4-dihydroxyphenylacetic acid, 4hydroxyphenylacetic acid, and 3,4-dihydroxybenzaldehyde (206).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that quercetin protects against neurodegenerative diseases by enhancing the mechanism of SIRT1 deacetylase (203,204). However, low bioavailability and solubility of quercetin limits its clinical application (205). In addition, most of the current studies only focused on quercetin glycosides, however, the functions of the gut micobiota helps to breakdown quercetin into serious biological metabolites such as phloroglucinol, 3,4-dihydroxyphenylacetic acid, 4hydroxyphenylacetic acid, and 3,4-dihydroxybenzaldehyde (206).…”
Section: Discussionmentioning
confidence: 99%
“…Cocrystals of quercetin with caffeine (QUE–CAF) and its methanol solvate (QUE–CAF·MeOH) exhibited 14 and 8 times higher solubility, whereas quercetin–theobromine dihydrate (QUETBR·2H 2 O) is slightly better than the stable quercetin dihydrate. Their dissolution profile is shown in Figure . , …”
Section: Design and Methodology Of Pharmaceutical Cocrystalsmentioning
confidence: 99%
“…Their dissolution profile is shown in Figure 44. 250,251 Four cocrystals of the model drug propylthiouracil (PTU) 252 for the treatment of hyperthyroidism, which has a short half-life, were demonstrated as sustained-release forms to overcome hepatotoxicity associated with rapid high drug concentration. Nutritional coformers cinnamic acid (CA), gentisic acid (GA), ellagic acid (EA), and kaempferol (KA) with PTU afforded cocrystals of excellent stability (at accelerated ICH conditions of 40 °C, 75% RH over 12 weeks), and PTU−CA, PTU−EA, PTU−KA cocrystals decelerated the intrinsic dissolution rate (IDR) due to their lower solubility.…”
Section: Drug-nutraceutical and Vitamins Cocrystalsmentioning
confidence: 99%
“…To investigate whether the plasma concentration of cocrystal in rats increased compared with API, we performed a pharmacokinetics experiment of cocrystal PRA-FA in vivo [ 26 , 27 ]. SD rats were randomly divided into three groups with two rats in each group.…”
Section: Methodsmentioning
confidence: 99%